The concepts on quality of life in the Maribor post-WW2 housing estates - Skalicky, Vanja (AR. Arhitektura, raziskave, 2012)
The paradigm of quality of life in housing depends on various interconnectedness functions, which satisfy not only the needs of dwellers but also the inhabitants of the city, in general. In addition, it is essential that the residential areas incorporate well accessible and appropriately designed open public space and green areas. In regard to that, the chapter focuses on the impacts of housing estate planning elements on quality of life. Currently, open public space and green areas in the post-WW2 housing estates are often used for other purposes, largely as a consequence of number of cars that has led to enormous parking problems. Two decades after the housing privatization, the question of the ownership of green areas and related maintenance is often the cause of most adverse conflicts, arising from the misuse of open public space. Further, a special phenomenon, the influence of high-quality Scandinavian housing models on Slovenian urban planning and design of housing estates in the post -WW2 period will be presented. The overview of multi-family housing estates in the city of Maribor from this period raise new approach on the quality of life particularly in regard to open public space.
Keywords: architect; arhitekti; green areas; Humek, Ljubo; javni prostor; kakovost življenja; Maribor; odprt javni prostor; open public space; post-WW2 housing estates; povojna gradnja; quality of life; standard of living; stanovanjska naselja; urbani prostor; zelene površine